Fixed Point Results for \((α\)-\(β_k,φ\)-\(ψ)\) Integral Type Contraction Mappings in Fuzzy Metrics - Tiwari, Rakesh; Rajput, Shraddha (Communications in Mathematics and Applications, 2021)
In this paper, we introduce the notion of a modified \((α\)-\(β_k,φ\)-\(ψ)\) integral type contraction mappings in fuzzy metric spaces. We study and prove the existence and uniqueness of fixed points theorems in generalized fuzzy contractive mappings of integral type in fuzzy metric spaces. Our main result generalizes the fuzzy Banach contraction theorem and we validate our results by some suitable examples which reveal that our results are proper generalization and modification of some researchers' integral contraction works.